Negative life events and internet addiction among college students: role of physical exercise and prosocial behavior - Huang, Qinyu; Li, Jingjing; Wang, Jiangyu; Liu, Bing (Frontiers in Psychology, 2025)
IntroductionThis study investigates the relationship between negative life events and Internet addiction, as well as the mediating role of prosocial behavior and the moderating role of physical exercise in this process among Chinese college students. Based on the Conservation of Resources Theory and Stress Coping Theory, we constructed a moderated mediation model to analyze the psychological mechanisms underlying students’ Internet addiction.MethodsA total of 259 undergraduate students from six universities in Shanghai participated in this study. Data were collected through standardized questionnaires and analyzed using moderated mediation analysis.ResultsProsocial behavior significantly mediates the relationship between negative life events and Internet addiction. Moreover, physical exercise at varying levels exerts differential moderating effects on the relationship between negative life events, prosocial behavior, and Internet addiction.DiscussionThese findings underscore the importance of promoting prosocial behavior and appropriate levels of physical exercise to mitigate the risk of Internet addiction among college populations.